Sulfonic Zwitterion for Passivating Deep and Shallow Level Defects in Perovskite Light‐Emitting Diodes. (23rd February 2022) - Zhang, Ju; Xing, Xuanchang; Qian, Dongmin; Wang, Airu; Gu, Lianghui; Kuang, Zhiyuan; Wang, Jingmin; Zhang, Hao; Wen, Kaichuan; Xu, Wenjie; Niu, Meiling; Du, Xuerong; et al.
Abstract: Chemical passivation via functional additives plays a critical role in achieving high performance perovskite light‐emitting diodes (PeLEDs). Here, perovskite composite films for high performance PeLEDs by using zwitterion 3‐aminopropanesulfonic acid (APS) as the additive are developed. The sulfonic group of APS can simultaneously passivate deep and shallow level defects in perovskites via coordinate and hydrogen bonding, which leads to suppressed non‐radiative recombination and ion migration in the perovskite composite films. Based on this, PeLEDs with a peak external quantum efficiency of 19.2% and a half‐lifetime of 43 h at a constant current density of 100 mA cm −2 are obtained, representing one of the most stable and efficient PeLEDs under high current densities. Abstract : High performance perovskite LEDs can be achieved by using sulfonic zwitterion which simultaneously passivates deep and shallow level defects of perovskite via chemical bonding.